2006
DOI: 10.1016/j.ijsolstr.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithm optimization of phononic bandgap structures

Abstract: This paper describes the use of genetic algorithms (GAs) for the optimal design of phononic bandgaps in periodic elastic two-phase media. In particular, we link a GA with a computational finite element method for solving the acoustic wave equation, and find optimal designs for both metal-matrix composite systems consisting of Ti/SiC, and H 2 O-filled porous ceramic media, by maximizing the relative acoustic bandgap for these media. The term acoustic here implies that, for simplicity, only dilatational wave pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…[10][11][12][13]) some of which addressed porous topologies [14,15]. Two other works reported optimized porous topologies for maximized RBW of asymmetric guided wave modes through genetic algorithm (GA) [16] and gradient based [17] approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13]) some of which addressed porous topologies [14,15]. Two other works reported optimized porous topologies for maximized RBW of asymmetric guided wave modes through genetic algorithm (GA) [16] and gradient based [17] approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Promising applications of PnCs include sound insulation, 3 sound barrier, 4 damping, 5,6 acoustic resonators, 7,8 elastic/acoustic waveguides, 9 filters, 10 frequency sensing, 11,12 acoustic mirrors, 13 switches, 14 lenses, 15 energy harvesting, 16 negative refraction, 17,18 self-collimation, 19,20 acoustic mirages, 14 rectification, 21 acoustic diodes, 22,23 and thermal conductance. 24,25 In recent years, some researchers have been conducted and focused on topology optimization of photonic crystals (PtCs), 26,27 PnCs [28][29][30][31][32][33] and phoxonic crystals (PxCs). 34 Recent studies have shown that the topology optimization can greatly enhance the performance of PnCs, not only for bulk waves, [28][29][30][31][32][33][34] but also for surface waves 35 and plate waves.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 In recent years, some researchers have been conducted and focused on topology optimization of photonic crystals (PtCs), 26,27 PnCs [28][29][30][31][32][33] and phoxonic crystals (PxCs). 34 Recent studies have shown that the topology optimization can greatly enhance the performance of PnCs, not only for bulk waves, [28][29][30][31][32][33][34] but also for surface waves 35 and plate waves. 36 However, because of the high computational effort and the complex optimization procedure, most topology optimizations of bandgap maximization assumed that the unit-cell has a primary high-symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations